Indonesian Law and Artificial Intelligence: Balancing Accountability, Ethics, and Innovation - Hasibuan, Rangga Hotman; Rawung, Aurelya Jessica; Wowiling, Fidel Jeremy (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2024)
Artificial intelligence (AI), which includes computing for perception, cognition, and action, raises complicated legal issues. This research investigates AI’s influence and legal implications, focusing on its autonomy in communication and creativity, which raises problems about language, intellectual property, and ethical accountability. Discussions differ depending on whether they are influenced by the Common Law or Civil Law systems. While Common Law defines AI as “computer-generated work,” Civil Law tends to see AI as a legal thing. This research aims to formulate a solid ground for an AI legal framework in the Indonesian national legal system. The research undertaken involves a thorough analysis of academic literature, focusing on the legal and ethical implications of AI, highlighting the need for a nuanced perspective to define its subjectivity. In conclusion, the complex interplay between artificial intelligence (AI) and legal principles involves reframing old terminology. Existing models for AI duty are called into question, and vicarious liability is one possible answer. AI is a derived law problem, so it needs to be carefully calibratedfor responsible innovation while also keeping ethics and technological progress in check.